Visual Analytics Research at Universidade Federal do Ceará - Santos, Emanuele; Neto, José F. de Queiroz; Gomes, George A. M.; Leite Junior, Antonio José M.; Cavalcante Neto, Joaquim Bento; Vidal, Creto Augusto; Silva, Ticiana L. Coelho da; Macedo, Jose Antonio F. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais Estendidos da XXXIV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2021.20048, 2021)
In this paper, we describe the research in visual analytics that is a partnership between two research groups at the Federal University of Ceara, CRAB – Computer Graphics, Virtual Reality, Animation, and Visualization Group and Insight Data Science Lab. This fruitful collaboration joined CRAB’s expertise in Visualization with Insight Lab’s expertise in Data Science to bring about valuable research and development projects in the public and private sector in many areas, including crime analysis, mobility data visualization, education, and games. We briefly describe our main projects in these areas and their social, technological, and scientific contributions in the following sections.